Profile and knowledge of Brazilian Amazon Primary Health Care professionals on maternal and child health - Bruna Melo Amador; Emanuele Rocha da Silva; Víctor Almir Leão Fortunato; Raissa Lorrana Bronze Coelho; Katiane da Costa Cunha; Aurimery Gomes Chermont (Centro Brasileiro de Estudos de Saúde, 2023)
ABSTRACT This study aimed to evaluate the social and professional profile and knowledge of Primary Care professionals on maternal and child health. Cross-sectional descriptive study, from May to July 2018. It included 30 nurses and 73 Community Health Workers (CHW) from the municipality of Bragança, Pará. The form had three phases: participants' profile; close-ended questions on their profile, knowledge and resourcefulness on the First Week of Integral Care guideline; and four open-ended questions. Quantitative data was analyzed through Microsoft Office ExcelTM 2016, as qualitative data was arranged through word clouds and similarity trees in IRaMuTeQTM. The majority of nurses and CHW were female (70.9%) and worked in urban areas (60.2%), as 40% of nurses were graduated recently, with an 80% specialization courses, and 83.6% CHW had completed high school. On both categories, 82.5% did not know the First Week of Integral Health guideline, although the word clouds and similarity trees had shown that several national standardized orientations were provided. First Week of Integral Care guidelines' insufficient knowledge by nurses and CHW in the municipality points to fragility in Primary Care on maternal and child health. Although basic orientations are provided, improvement is necessary.